Transfer of Ownership on the Assets of a Company to the Partners in Case of Liquidation. Practical Aspects - Simona Petrina GAVRILA; Florin TUDOR; Stefania Cristina Mirică (Communications of International Proceedings, 2021)
The company, like any natural or legal person, has a limited existence in time, and its liquidation may involve the allocation of assets to former partners, as its successors. The Romanian law contains norms that regulate these aspects, but, in practice, problems have arisen either from the inability of the associates to acquire the right of ownership over the lands, or from their omission to solve the situation of some goods prior to the deregistration of the company. The purpose of this article is to analyze the problems indicated above and to propose appropriate practical solutions.
Keywords: The deregistration of the company; company assets; transfer of ownership; Romanian legislation; financial interests.